Apologizing Strategies Used By The Students Of EnglishDepartment Of Muhammadiyah University Of Surakarta - Ariyanti Rodiah, Hindria, dra.Siti Zuhriah Ariatmi. M.Hum (2017)
This study aims at describing (1) the apologizing strategies of the utterance, and (2) the politeness strategies of the apologizing utterance used by the students. The data of this study are the utterances which are used by the students. The technique of collecting data is DCT model. The techniques for analyzing data are analysis, discussion, and conclusion. The data are analyzed by using apologizing strategies theory of Trosborg (1995) and politeness strategies by using theory of Brown and Levinson (1987). The researcher found that: (1) there are twenty seven types of apologizing strategies which are combined with the other strategies and other utterances by the students. The types of Trosborg's apologizing strategies are not independent because they are used together by the students. The students have their own ways to choose the utterances for expressing apology to the hearer. The students combine apology with other utterances, namely: thanking, warning, asking punishment, asking for feeling, offering the future acceptance, and persuading the hearer. They mostly use combination of promise for forbearance for the hearer who has lower power and they use combination of explicit explanation for the hearer who has equal and higher social status. There are 44% students who use apologizing strategy appropriately and 56% students who use apologizing strategy inappropriately. There are 56% students who are fail to choose appropriate apologizing strategies in relation with power property of the speakers, relative age between the speakers, seriousness of the case, and behavior, (2) there are three types of politeness strategies namely: bald on record strategy takes 4%, positive politeness strategy takes 64%, and negative politeness strategy takes 32%. There are 59% students who use politeness strategy appropriately and 41% students who use politeness strategy inappropriately. There are 41% students who are fail to choose appropriate politeness strategies in relation with relative distance between the speakers and in relation with behavior. They mostly use negative politeness strategy for the hearer who is familiar-equal and unfamiliar-lower. Keywords: apologizing strategies, politeness strategies.